2013
DOI: 10.1093/eurheartj/eht131
|View full text |Cite
|
Sign up to set email alerts
|

Circulating platelet-progenitor cell coaggregate formation is increased in patients with acute coronary syndromes and augments recruitment of CD34+ cells in the ischaemic microcirculation

Abstract: These findings imply that circulating platelet/CD34+ cell coaggregate levels are increased in ACS, especially in STEMI, which may be a novel mechanism of domiciliation of CD34+ progenitor cells to the injured microvasculature after acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…49 However, platelet-induced differentiation of CD34-positive progenitors into mature foam cells and endothelial cells has been described in an in vitro co-culture system, 50 which may be of particular relevance for development of atherosclerotic vascular lesions.…”
Section: Platelet/progenitor Cell Interaction and Regenerationmentioning
confidence: 99%
“…49 However, platelet-induced differentiation of CD34-positive progenitors into mature foam cells and endothelial cells has been described in an in vitro co-culture system, 50 which may be of particular relevance for development of atherosclerotic vascular lesions.…”
Section: Platelet/progenitor Cell Interaction and Regenerationmentioning
confidence: 99%
“…Moreover, activated platelets can also bind to injured endothelial cells. It has been reported that platelet activation starts as early as 2 mins post-reperfusion after 45 mins of ischaemia 24 , and activation and recruitment of platelets can persist for days to weeks after MI injury 9 . Our data suggest that PNV decoration resulted in a boost of CSC retention in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Various platelet surface molecules such as glycoprotein (GP)VI, GPIV, GPIb, GPIX, GPV and GPIIb/IIIa are involved in platelet recruitment 8 . It has previously been reported that platelets could form co-aggregates with circulating CD34+ progenitors in patients with acute coronary syndromes, and these co-aggregates improve prognosis by promoting peripheral recruitment of CD34+ cells in the ischaemic microcirculatory area and boosting their adhesion to the vascular lesion 9 .…”
mentioning
confidence: 97%
“…It has been well established that platelets interact with and adhere to EPCs and mature endothelial cells [5,14,16,17,18,19,21,54]. Therefore, we further studied the adhesion of platelets to passage 4 OECs (which exhibited the highest anti-platelet activity in the aggregation studies) versus to CD34+ and HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating CD34+ cells contribute to cardiovascular homeostasis in a paracrine way or through differentiation into endothelial cells and smooth muscle cells in vivo [5,6,7]. These cells are increased in the peripheral blood of patients with acute myocardial infarction, and are rapidly recruited to the myocardium, mediating a protective effect of ischaemic preconditioning [5,8,9,10]. The peripheral recruitment of circulating progenitor cells is a multi-step process that includes chemoattraction, migration, adhesion, and tissue invasion [5,7].…”
Section: Introductionmentioning
confidence: 99%